Importance of critical care staffing and standard intensive care therapy in the COVID-19 era: a descriptive study of the first epidemic wave at a Swiss tertiary intensive care unit (Swiss Medical Weekly, 2021)
AIM Mortality rates of COVID-19 patients hospitalised in intensive care units (ICUs) are generally high. Availability of ICU resources might influence clinical outcomes. The aim of this study was to examine the clinical course of the 42 patients treated during the first epidemic wave between 2 March and 20 May 2020 at the tertiary ICU of the Bern University Hospital, where staffing, equipment and drugs were not limited. METHODS For this descriptive study, retrospective data of the first COVID-19 wave in an interdisciplinary adult ICU of a Swiss University hospital was used. The study included data regarding healthcare staffing and COVID-19 patients. The primary outcome was the ICU mortality in COVID-19 patients. RESULTS Patients’ median age was 61 years (range 32–86), simplified acute physiology score (SAPS-II) was 46 (13–90), 81% of the patients were males, 79% were mechanically ventilated (3 of them on extracorporeal membrane oxygenation), 31% were under renal replacement therapy and 21% received steroids. All patients were fully anticoagulated from the time of admission. No off-label experimental antiviral or anti-inflammatory drugs were used with the exception of one patient, and antibiotic prescription was restrictive. Nurse-to-patient ratio was 1:1 during all shifts, and the physician-to-patient ratio was 1:4 (day shift) and 1:10 (night shift). Infectious disease specialists and physiotherapists were present every day. The median ICU length of stay was 10 days (1–38) days, and ICU and hospital mortality rates were 7% and 12%, respectively. CONCLUSION Careful intensive care treatment, without off-label drug use but including steroids in selected cases, combined with an interdisciplinary approach and provision of sufficient human resources, were associated with low ICU and hospital mortality rates despite high disease severity. Availability of qualified human resources may have an important impact on the outcome of COVID-19.